Enhanced mechanical properties and biocompatibility on BC/HAp composite through calcium gluconate fortified bacterial. (1st April 2022) - Shi, Lin; Wang, Tao; Yang, Lei; Chen, Chuntao; Dou, Ran; Yang, Xiaoli; Sun, Bianjing; Zhou, Baojing; Zhang, Lei; Sun, Dongping
Abstract: Bacterial cellulose/hydroxyapatite (BC/HAp) composite is an outstanding candidate for bone tissue engineering. The conventional biomimetic mineralization method takes a long time with unsatisfactory mechanical properties and biocompatibility. Herein, we modified the BC by changing the carbon source to calcium gluconate during the biosynthesis process of BC by bacteria, providing nucleation sites for further mineralization in simulated body fluid. Results show spherical porous HAp in the size of 100–200 nm was fully filled in the three-dimensional network structure of BC nanofibers uniformly within five days of mineralization. Molecular dynamics simulation shows that the aggregation of cellulose units in aqueous solution can enhance the adsorption of calcium ions. By this means, we significantly improved the mechanical properties and biocompatibility of the BC/HAp composite, as well as simplified the preparation process, compared to conventional method, which, therefore, suggests, it could be further studied for biomedical applications such as bone tissue engineering. Graphical abstract: We modified the bacterial cellulose with calcium ions by changing the carbon source to calcium gluconate during the biosynthesis process of BC, which provides nucleation sites for further mineralization of hydroxyapatite. This method significantly improves the mechanical properties and biocompatibility of the BC/HAp composite compared to those made from conventional method, which, therefore, suggests it could be further studied for biomedical applications such as bone tissue engineering. Unlabelled Image